2013
DOI: 10.1007/s00586-013-2732-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of minimally invasive fusion and instrumentation versus open surgery for severe stenotic spondylolisthesis with high-grade facet joint osteoarthritis

Abstract: Purpose The object of this study was to compare minimally invasive surgery (MIS) with open surgery in a severely affected subgroup of degenerative spondylolisthetic patients with severe stenosis (SDS) and high-grade facet osteoarthritis (FJO). Methods From January 2009 to February 2010, 49 patients with severe SDS and high-grade FJO were treated using either MIS or open TLIF. Intraoperative and diagnostic data, including perioperative complications and length of hospital stay (LOS), were collected, using retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 29 publications
(53 reference statements)
0
53
0
Order By: Relevance
“…This provides adequate exposure through which a unilateral facetectomy, annulotomy, and disc space preparation can be performed. MIS approaches to the TLIF have been developed with the goals of decreasing surgical morbidity, decreasing hospital stay, and hastening recovery [1,3,8,12]. However, concerns remain about the adequacy of the disc space preparation in a minimally invasive approach to the TLIF [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This provides adequate exposure through which a unilateral facetectomy, annulotomy, and disc space preparation can be performed. MIS approaches to the TLIF have been developed with the goals of decreasing surgical morbidity, decreasing hospital stay, and hastening recovery [1,3,8,12]. However, concerns remain about the adequacy of the disc space preparation in a minimally invasive approach to the TLIF [16].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, with the advent of sophisticated retractor systems and instrumentation, minimally invasive approaches to the TLIF have become popular in an attempt to decrease surgical morbidity and length of hospital stay and hasten recovery [1,3,8,12]. However, concerns remain regarding the adequacy of disc space preparation that can be achieved through a minimally invasive approach to TLIF [16].…”
Section: Introductionmentioning
confidence: 99%
“…The operating time for the mTLIF was ranged from 116 to 390 minutes, compared with 102 to 365 minutes for oTLIF, the operating time tended to be longer in the mTLIF group than the oTLIF group (n = 11 studies) [10][11][12][16][17][18][19][20][21][22][23]. The estimated blood loss was generally and significantly lower in the mTLIF group, ranging from 51 to 578 ml in mTLIF and 225 to 961 ml in oTLIF, respectively (n = 13 studies) [10][11][12][13][15][16][17][18][19][20][21][22][23].…”
Section: Surgical Outcomesmentioning
confidence: 96%
“…The articles that included revision surgery (8) or more than a single level treated (6) or without the complications were also excluded. Eventually, 14 studies which met our inclusion criteria were included in the present systematic review [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The selection process for articles included in the review is shown in Fig.…”
Section: Study Identification and Selectionmentioning
confidence: 99%
“…15, 81377 Munich, Germany e-mail: cbirkenm@med.uni-muenchen.de [2] as well as for those treated with instrumented posterolateral fusion [3].…”
mentioning
confidence: 99%